Viabilidade do plasma frio atmosférico na inativação da alternaria sp - Lima, Lázaro José Alves de (Universidade Federal Rural do Semi-Árido, 2018)
In this study, treatments with different times, between 1 and 15 minutes, were used to inactivate spores of Alternaria sp. isolated from Papaya Formosa, since this microorganism is a common and frequent cause of economic losses for exporting companies in Brazil. A fungal suspension was treated with cold atmospheric DC plasma. An electric discharge was produced with 10 kV and 20 kV voltage pulses, repeated at a frequency of 15.5 kHz, applied inside a test tube containing the spore suspension of Alternaria sp. (5x10³ conidia.mL-1). The efficiency of the plasma treatment was compared with the efficiency of a sanitizer (sodium dichloro isocyanurate 400 ppm) and a fungicide (quaternary ammonium, 1000 ppm). The suspension of spores of Alternaria sp. was analyzed for its pH and oxidation potential (REDOX). Reduction of pH and increase of redox potential proportional to treatment time and plasma energy demand were observed. Optical emission spectroscopy (OES) was used to identify and monitor the species present in the plasma-liquid system. It was found that the plasma was more efficient than the fungicide and comparable to the sanitizer. Application times of 3 min (20 kV) and 9 min (10 kV) were sufficient for complete inactivation of fungi. The results indicate that plasma treatments have efficiency against fungal spores and that this energy source is promising in food science
Keywords: descarga elétrica; antifúngico; antimicrobiano; dicloro; fungicida; electric shock; antifungal; antimicrobial; dichloro; fungicide; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA